1977
DOI: 10.1073/pnas.74.7.2855
|View full text |Cite
|
Sign up to set email alerts
|

Extensive disulfide bonding at the mammalian cell surface.

Abstract: Cell surface proteins of cultured cells are disulfide bonded to a greater degree than are total cellular proteins. In particular, the "large external transformation-sensitive" (LETS) protein, a major surface protein, is present almost exclusively in disulfide-bonded complexes including homodimers and also higher aggregates held together bydisulfide bonds or noncovalent interactions. Other cell surface proteins also appear to be involved in disulfide bonding, both intramolecular and intermolecular. In virally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1

Year Published

1978
1978
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(60 citation statements)
references
References 38 publications
1
58
1
Order By: Relevance
“…The basis for this congruence of location may be the recently described noncovalent interactions of FN with other FN molecules (44) and with collagen (18). FN crosslinks with itself and other proteins through disulfide links (9,45). FN on cell surfaces is known to be immobile and may serve as an anchorage point for cell attachment (44).…”
Section: Discussionmentioning
confidence: 99%
“…The basis for this congruence of location may be the recently described noncovalent interactions of FN with other FN molecules (44) and with collagen (18). FN crosslinks with itself and other proteins through disulfide links (9,45). FN on cell surfaces is known to be immobile and may serve as an anchorage point for cell attachment (44).…”
Section: Discussionmentioning
confidence: 99%
“….,S behavior (27)(28)(29). Even if fibronectin is closely related to the regulatory processes involved in collagenase secretion, it is not surprising that its exogenous addition did not inhibit the induced secretion or restore altered morphology, because it has recently been shown that little fibronectin adheres to the surface of normal cells once it is shed into conditioned medium (8,30).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3]. Purified cellular fibronectin exists predominantly as dimers and multimers of 440,000 daltons and larger (4,5). A similar subunit organization characterizes the fibronectin located on the cell surface (4)(5)(6)(7).…”
mentioning
confidence: 99%